Exercise, addiction and motivation: the development of a motivation scale in extreme sports as a sport of challenge with nature - Karakulak, İzzet; Yavaş, Özge; Bora, Mehmet Veysi; Eyuboğlu, Ender; Aslan, Cem Sinan; Aydemir, Ahmet; Dinç, Sırrı Cem; Karakullukçu, Ömür Fatih; Öz, Faik; Şahin, Fatma Neşe (Frontiers in Psychology, 2025)
In the extant literature, the concepts of motivation and addiction have been employed to elucidate how a considerable number of unpleasant experiences for extreme sports participants can eventually become rewarding. The objective of this study was to develop a scale to measure the behavioral addiction levels of extreme sports athletes. A plethora of addiction and motivation scales (MS) exists; however, none of them are measurement tools that can assess emotional responses and simultaneously address motivation and addiction. Moreover, they are not specific to extreme sports participants. The present study comprised 1,073 participants engaged in extreme sports and incorporated psychometric analyses encompassing a literature review, expert review, exploratory and confirmatory factor analysis. The MS factor structure was determined using the Principal Axis Factoring (PAF) method. The analysis yielded a three-factor structure comprising 16 items, accounting for 63.00% of the total variance. In order to validate the structure, first- and second-order factor analysis was performed. The fit indices obtained at both levels were consistent with the acceptable limits specified in the literature. In the final results, 16 items related to three factors, namely “hedonic deprivation,” “tolerance,” and “hedonic opposition,” were validated. Furthermore, the AVE, CR, and √AVE values were calculated. The analysis results indicated that each sub-dimension in the measurement model exhibited a distinct structure and fulfilled the established validity criteria. Cronbach’s Alpha and Split-Half coefficients were calculated to ascertain the reliability of the measurement. The floor and ceiling effects of the MS were also examined. Finally, ROC analysis was employed to evaluate the measurement tool. The findings of this research indicate that the MS, which has been developed and comprises 16 items and a three-factor structure, is a valid and reliable instrument capable of simultaneously addressing motivation and addiction in the context of extreme sports. The scale is of significance as it is the inaugural quantitative measurement tool with the capacity to assess addiction. In conclusion, the MS provides a novel, theory-based contribution to the literature by integrating motivation and behavioral addiction within a single, psychometrically validated framework specific to extreme sports.